IMPLEMENTASI VIRTUAL LEARNING POLTEKKES KEMENKES KUPANG - Waaangsir, Ferry WF; Saleh, Ummi Kaltsum S; Kusmiyati, Kusmiyati; Nugraha, Yohanes C (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
The COVID-19 pandemic requires the learning system to be carried out online. One of the online learning methods developed by "Badan PPSDM Kesehatan implemented by Poltekkes Kemenkes Kupang is VILEP or Virtual Learning Poltekkes. This studi aims to obtain an overview of the implementation of learning using VILEP at Poltekkes Kemenkes Kupuang. The research was conducted by survey with an observational descriptive design. The implementation of VILEP at the Health Poltekkes of the Ministry of Health of Kupang has been implemented since 2018. In the odd semester of the 2021/2022 academic year, the average VILEP realization courses has only reached 31,47%; while the average implementation of VILEP has only reached 52.38%. Efforts to re-socialize, mentoring by VILEP admins and training on digital teaching materials are the main points to maximize lecturers' readiness to use VILEP in further learning.